Marginalization of the Margins: The Importance of Smaller Islands in Human Prehistory. (3rd May 2016) - Fitzpatrick, Scott M.; Thompson, Victor D.; Poteate, Aaron S.; Napolitano, Matthew F.; Erlandson, Jon M.
ABSTRACT: Across the world's seas and oceans, archaeological research focused on islands has generally privileged those that are larger in size. Explanations for this phenomenon range from the (mis)perception by scholars that prehistoric peoples were more attracted to the presumed greater number and diversity of resources typically available on larger islands, to the ephemeral aspect of archaeological evidence on smaller land areas. These are coupled with logistical and infrastructure issues that often limit access to labor, equipment, and transportation to conduct field activities (e.g., remote atolls in the Pacific). A growing body of research demonstrates, however, that ancient peoples regularly and readily occupied and/or accessed many smaller islands for both terrestrial and marine resources. In some cases, within an archipelago, evidence shows an earlier occupation on smaller islands versus larger ones, or an attraction to the former given unique or seasonal resource availability and/or defensive capabilities. We describe cases from several areas of the world that highlight the importance of relatively small islands (∼1–500 km 2 ) for understanding human adaptations in what many have considered to be among the most marginal of environments.